Azathioprine for refractory ulcerative proctitis: A retrospective multicenter study. Issue 3 (March 2017) - Mallet, Anne-Laure; Bouguen, Guillaume; Conroy, Guillaume; Roblin, Xavier; Delobel, Jean-Bernard; Bretagne, Jean-François; Siproudhis, Laurent; Peyrin-Biroulet, Laurent
Abstract: Background: Efficacy of azathioprine (AZA) in refractory ulcerative proctitis (UP) is unknown. Methods: All patients treated with AZA for refractory UP in three referral centers between 2002 and 2012 were included. "Treatment success" in the long-term was defined as the absence of colectomy during follow-up, no need for anti-TNF during follow-up, no ongoing systemic steroids use, no adverse event leading to AZA withdrawal, and clinically quiescent disease at last follow-up. Results: Of the 1279 adult patients with ulcerative colitis, 25 patients were treated with AZA for refractory UP (median disease duration 4.9 years). Of these, 4 had no short-term clinical assessment. Of the remaining 21, 4 were primary non responders to AZA, 7 discontinued AZA for adverse events and 10 showed clinical improvement. At the long-term assessment at last follow up after a median of 46 months, 5 patients had treatment success and were still on AZA treatment, the remaining 20 were treatment failures. Of these, 5 discontinued AZA for adverse events and 15 were treated with infliximab (clinical response in 11 patients, primary non-response in one patient, and 3 underwent colectomy). Conclusion: AZA may be efficacious in maintaining clinical response in one-fifth of patients with refractory UP in a real-life setting.